Gloria mundi - Papatakis, Nico; Lafaye, Yves; Le Saux, Yorick; Pradier, Jean-Paul; Rizzotti, Benoît; Variot, Frédéric; Karlatos, Olga; Bertin, Roland; Adrien, Philippe (Nico Papatakis - L'intégrale Blu-ray, 2015)
In order to justly portray a torture victim for a film on the Algerian War, Galai starts to systematically mistreat herself. She burns her breasts with cigarettes, subjects herself to electric shocks - does to her body and soul all the things that were done to people back then. But, is the war really over? And who are the armies of the night moving through the streets of Paris? One of the most disturbing pieces of cinema from the 70s, which at the time only a few saw - the film got a reputation as being simply too much. In 2004, Nikos Papatakis re-edited parts of the film, shot a few new scenes, added some ghostly digital effects - adding layer upon layer to an already complex and challenging cinematic text. A one-of-a-kind work. [iffr.com]